Pediatric NMOSD: A Review and Position Statement on Approach to Work-Up and Diagnosis - Silvia Tenembaum; E. Ann Yeh; The Guthy-Jackson Foundation International Clinical Consortium (GJCF-ICC); Hesham Abboud; Raed Alroughani; Ayse Altintas; Lilyana Amezcua; Metha Apiwattanakul; Nasrin Asgari; Brenda Banwell; Jeffrey Bennett; Denis Bichuetti; et al. (Frontiers Media S.A., 2020)
Neuromyelitis Optica Spectrum Disorder (NMOSD) is an inflammatory demyelinating disease of the central nervous system (CNS) primarily affecting the optic nerves and spinal cord, but also involving other regions of the CNS including the area postrema, periaqueductal gray matter, and hypothalamus. Knowledge related to pediatric manifestations of NMOSD has grown in recent years, particularly in light of newer information regarding the importance of not only antibodies to aquaporin 4 (AQP4-IgG) but also myelin oligodendrocyte glycoprotein (MOG-IgG) in children manifesting clinically with this syndrome. In this review, we describe the current state of the knowledge related to clinical manifestations, diagnosis, and chronic therapies for children with NMOSD, with emphasis on literature that has been published in the last 5 years. Following the review, we propose recommendations for the assessment/follow up clinical care, and treatment of this population.